Chironji is promising fruit for tribals - Singh, Sanjay; Singh, A K; Mishra, D S; Rao, V V Appa; Saroj, P L (Indian Horticulture, 2019)
Chironji, a priced dry fruit, is grown naturally by seed in mixed dry deciduous forests of tropics and subtropics. The Thar Priya variety of chironji, developed by this centre for high yield and kernels production, is multiplied by softwood grafting technique. Vegetatively propagated plants of Thar Priya are being prepared for farmers. It is remunerative fruit tree for dryland horticulture.